2016
DOI: 10.1002/path.4718
|View full text |Cite
|
Sign up to set email alerts
|

CD169 + macrophages mediate pathological formation of woven bone in skeletal lesions of prostate cancer

Abstract: Skeletal metastases present a major clinical challenge for prostate cancer patient care, inflicting distinctive mixed osteoblastic and osteolytic lesions that cause morbidity and refractory skeletal complications. Macrophages are abundant in bone and bone marrow and can influence both osteoblast and osteoclast function in physiology and pathology. Herein, we examined the role of macrophages in prostate cancer bone lesions, particularly the osteoblastic response. First, macrophage and lymphocyte distributions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
(88 reference statements)
2
29
0
Order By: Relevance
“…As we have also previously reported osteomac presence in calvarial osteal tissue, 1 and others have shown macrophage contributions to calvarial injury repair, this cellular mechanism applies to both flat and long bones. Our evidence that osteomacs are present in human osteal tissues 1 , 47 provides support that this biology is not a species‐specific phenomenon. Definitive dissection of the specific roles of macrophages and osteoblasts in bone formation and repair was recently revealed to be more challenging than traditionally appreciated as macrophage can be resistant to lethal doses of irradiation 48 .…”
Section: Discussionsupporting
confidence: 56%
“…As we have also previously reported osteomac presence in calvarial osteal tissue, 1 and others have shown macrophage contributions to calvarial injury repair, this cellular mechanism applies to both flat and long bones. Our evidence that osteomacs are present in human osteal tissues 1 , 47 provides support that this biology is not a species‐specific phenomenon. Definitive dissection of the specific roles of macrophages and osteoblasts in bone formation and repair was recently revealed to be more challenging than traditionally appreciated as macrophage can be resistant to lethal doses of irradiation 48 .…”
Section: Discussionsupporting
confidence: 56%
“…For example, in BM EIM are particularly susceptible to clodronate liposomes [16], but granulocytes [16] and myeloid precursors are preserved. Both osteomacs and osteoclasts are efficiently depleted by clodronate liposomes [26]. An additional nuance of this model is that delivery route and delivery dose/regimen impact on the macrophage depletion specificity and sensitivity including target organ variation [21,23].…”
Section: In Vivo Models Of Macrophage Depletionmentioning
confidence: 99%
“…Thus DTR expression is regulated by the endogenous CD169 promoter. CD169 expression is restricted to a subset of tissue macrophages and is expressed by approximately 30% of BM F4/80 + cells which includes HSC niche macrophages [28], EIM [24] and osteomacs [26]. This model avoids many undesired off-macrophage targets, including osteoclasts [26].…”
Section: In Vivo Models Of Macrophage Depletionmentioning
confidence: 99%
“…4,19,32 Otherwise, previous study showed the elder RAW264.7 cells could change its morphology and decrease the production of proteins, which lead RAW264.7 cells resistant for differentiation and transduction. [45][46][47] Otherwise, the CD11c and iNOS in subpanel-1 are demonstrated as highly expressed in pro-inflammatory macrophage stage (M1). Therefore, combined with previous excellent and novel studies in these fields, 4,32 in our experiences, it might be a reason for different RAW-OC induction efficacies among various study groups.…”
Section: Phenot Ype S Tudy Of R Aw26 47 and Its Role On The Reg Ulmentioning
confidence: 99%
“…32 However, comparing to RAW264.7, the bone marrow macrophage-M0 (BMM-Mφ) has been reported markedly express CD169. [45][46][47] Otherwise, the CD11c and iNOS in subpanel-1 are demonstrated as highly expressed in pro-inflammatory macrophage stage (M1). 48 Similarly, genes in subpanel-2 and subpanel-3 also associated with macrophage activation including: CD86, HIF-1α, CD11a, CD18, CD206, CD200R, Glut1 (Glucose transporter 1) and Ly6c and TfR2, Arg1 and SCARA-5b (scavenger receptor class A member 5) respectively.…”
Section: Phenot Ype S Tudy Of R Aw26 47 and Its Role On The Reg Ulmentioning
confidence: 99%